THE EFFECT OF THE FLIPPED CLASSROOM MODEL ON STUDENTS’ WRITING SKILL IN CLASS XI SMA NEGERI 18 MAKASSAR - Rasniati Guhir; Rampeng; Ulfah Syam (Lembaga Jurnal FKIP Universitas Bosowa, 2022)
This study aimed to know the effect of the flipped classroom model on students' writing skill in class XI SMA Negeri 18 Makassar. This study focused on pre-experimental research one group pre-test and post-test. The population in this study were students of class XI SMAN 18 Makassar. The writer took 270 students as the population. A random sampling technique was used to take one class as the research sample, totaling 30 students. Data obtained from writing test. The results of this study used inferential analysis of the t-test by SPSS v.16, which showed a significant effect on the students’ mean score writing skill between the pretest and post-test. The mean score of the students’ writing enhanced from 52.33 in the pretest to 82.03 in the posttest. The significance value calculated 0.000 is smaller than 0.05 (P-value = 0.000 < 0.05). Thus, it can be concluded that the flipped classroom model is effect applied to students’ writing skill in class XI at SMA Negeri 18 Makassar.